Alcohol Co-Administration Changes Mephedrone-Induced Alterations of Neuronal Activity - Grotell, Milo; den Hollander, Bjørnar; Jalkanen, Aaro; Törrönen, Essi; Ihalainen, Jouni; de Miguel, Elena; Dudek, Mateusz; Kettunen, Mikko I.; Hyytiä, Petri; Forsberg, Markus M.; Kankuri, Esko; Korpi, Esa R. (Frontiers in Pharmacology, 2021)
Mephedrone (4-MMC), despite its illegal status, is still a widely used psychoactive substance. Its effects closely mimic those of the classical stimulant drug methamphetamine (METH). Recent research suggests that unlike METH, 4-MMC is not neurotoxic on its own. However, the neurotoxic effects of 4-MMC may be precipitated under certain circumstances, such as administration at high ambient temperatures. Common use of 4-MMC in conjunction with alcohol raises the question whether this co-consumption could also precipitate neurotoxicity. A total of six groups of adolescent rats were treated twice daily for four consecutive days with vehicle, METH (5 mg/kg) or 4-MMC (30 mg/kg), with or without ethanol (1.5 g/kg). To investigate persistent delayed effects of the administrations at two weeks after the final treatments, manganese-enhanced magnetic resonance imaging brain scans were performed. Following the scans, brains were collected for Golgi staining and spine analysis. 4-MMC alone had only subtle effects on neuronal activity. When administered with ethanol, it produced a widespread pattern of deactivation, similar to what was seen with METH-treated rats. These effects were most profound in brain regions which are known to have high dopamine and serotonin activities including hippocampus, nucleus accumbens and caudate-putamen. In the regions showing the strongest activation changes, no morphological changes were observed in spine analysis. By itself 4-MMC showed few long-term effects. However, when co-administered with ethanol, the apparent functional adaptations were profound and comparable to those of neurotoxic METH.